2021
DOI: 10.1016/j.ijid.2020.11.167
|View full text |Cite
|
Sign up to set email alerts
|

Source attributed case-control study of campylobacteriosis in New Zealand

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…C. jejuni ST45 is one of the most frequently isolated strains of Campylobacter collected from humans, domestic animals and the environment [32][33][34]. It is regarded as a 'generalist' strain, as it has been isolated from multiple host species and environments [35,36], and has demonstrated frequent host switching [37].…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni ST45 is one of the most frequently isolated strains of Campylobacter collected from humans, domestic animals and the environment [32][33][34]. It is regarded as a 'generalist' strain, as it has been isolated from multiple host species and environments [35,36], and has demonstrated frequent host switching [37].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, considering Campylobacter spp. as a whole, most studies suggest that poultry or poultry followed by ruminants are the most prevalent sources [15][16][17][18][19][20][21]. Additionally, Liao et al found a positive correlation between rurality and ruminant-sourced campylobacteriosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of cases attributed to pork increased from approximately 20% in 2009-2016 to approximately 40% in 2017-2019, coinciding with a rise in cases due to Salmonella enterica ser 4,5,12:i:-, which has been found to be a persistent coloniser of pigs in Australia [33]. The proportion of cases attributed to layers was lower amongst rural-dwelling than urban-dwelling populations, similar to the rural-urban gradient found in a source attribution analysis of Campylobacter infections in New Zealand [20,34].…”
Section: Discussionmentioning
confidence: 63%